Sharh al-Hadith: Kajian Teoritis dan Metode atas Kitab Fath al-Bari - Fuad Arif Noor (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
Hadith of the Prophet have been around since the early development of Islam is a fact that no doubt, what was propped against the Prophet SAW. either Qawli, Fi’li, Taqrir, and that's the nature of the hadith. Understanding of textual starting from Fahm al-Hadith, Gharib al-Hadith to the Sharh al-Hadith. The book of Sharh al-Hadith is a description and interpretation as well as a comprehensive explanation of a manuscript or book which also includes comments lecturers book related to speech, action and behavior of the Prophet as well as chains and Matan of Hadith. Systematics of Fath al-Bari started from the explanation the name and background of the author, publishing history which consists of 15 chapters, and the first chapters written introduction to the publisher, the complete biography of Ibn Hajr and Sanad of Ibn Hajr to Sahih al-Bukhari, then he said the writing of the book Fath al-Bari. While the discussion explained the language problem and I’rab, and outlines the important issues that are not found in any other book, explains Balaghah and literary terms, taking the law and highlights the various issues being debated by scholars, both related to jurisprudence and theology detailed impartially. Recently gathered all Sanadof Hadis and examined, as well as describe the extent Sahih and Da’if.